Impacts of cattle farming practices and associated livestock systems on energy balances and greenhouse gas emissions in the municipality of Paragominas - State of Pará - Amazonia - Darlena Caroline da Cruz Corrêa; Darlena Caroline da Cruz Corrêa; René Poccard-Chapuis; Vincent Blanfort; Jean-Luc Bochu; Philippe Lescoat (Pastoralism)
Greenhouse gas (GHG) emissions and energy use are important parameters in the development of sustainable livestock systems. On-farm management practices can maximise energy efficiency and reduce gas emissions, however, these practices have yet to be identified and characterized. This study evaluated the eco-efficiency of cattle farming, considering a combination of the energy balance and GHG emissions from 33 farms in the Brazilian Amazon (Paragominas - Pará), using a diagnostic tool adapted to the region. The farms represented the diverse production systems operating in the area, distinguished by their activity (dairy, breeder, breeder-fattener and fattener), degree of intensification, and agrarian situation (corresponding to the farm’s geographical location and social and economic inclusion in the municipality). Energy efficiency on beef cattle farms is on average 16.29 GJ/t live weight (min = 1.74 GJ/t, max = 43.01 GJ/t), and on dairy farms 2.74 GJ/1000 L (min = 0.17, max = 6.48), i.e., respectively 46% and 40% lower than the figures reported by studies conducted in metropolitan France. Improved grazing enhances natural resources by optimising the use of forage biomass, which has a positive impact on energy efficiencies. The purchase of young animals and fertilisation account for a high percentage of energy consumption, with fuel constituting the major part of the direct energy consumed. GHG emissions are on average 17.40 teqCO2/t live weight (min = 6.13, max = 40.85), similar to those of metropolitan France (14 teqCO2/t). When emissions from livestock and storage by forests and pastures over 20 years of age are taken into account, farms have a positive carbon balance. The deforestation levels of each farm over the past 20 years have a strong impact on this balance sheet, which can make it negative. This study highlights the effectiveness of the method in identifying systems and practices that could help farms achieve greater sustainability in terms of energy use and GHG emissions.